2013
DOI: 10.1007/s00709-013-0592-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide is involved in maintaining ion homeostasis via regulating plasma membrane Na+/H+ antiporter system in the hydrogen peroxide-dependent manner in salt-stress Arabidopsis thaliana root

Abstract: Hydrogen sulfide (H2S) and hydrogen peroxide (H2O2) function as the signaling molecules in plants responding to salt stresses. The present study presents a signaling network involving H2S and H2O2 in salt resistance pathway of the Arabidopsis root. Arabidopsis roots were sensitive to 100 mM NaCl treatment, which displayed a great increase in electrolyte leakage (EL) and Na(+)/K(+) ratio under salt stress. The treatment of H2S donors sodium hydrosulfide (NaHS) enhanced the salt tolerance by maintaining a lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(63 citation statements)
references
References 53 publications
2
61
0
Order By: Relevance
“…In addition, NaCl stress inhibited seed germination and seedling growth, but pretreatment with NaHS could significantly attenuate this inhibitive effect and increase the ratio of potassium (K) to sodium (Na) in the root parts (Wang et al, 2012). Also, under 100 mM NaCl stress, Arabidopsis roots displayed a great increase in electrolyte leakage and Na + /K + ratio, indicating that Arabidopsis was sensitive to salt stress, while treatment with NaHS enhanced the salt tolerance by maintaining a higher K + /Na + ratio (Li J. et al, 2014). In addition, the level of gene expression and the phosphorylation of plasma membrane H + -ATPase and Na + /H + antiporter protein was promoted by H 2 S, while the effect of H 2 S on the plasma membrane Na + /H + antiporter system was removed by diphenylene iodonium (DPI, a PM NADPH oxidase inhibitor) or dimethylthiourea (DMTU, an ROS scavenger) (Li J. et al, 2014), suggesting that H 2 S can maintain ion homeostasis in salt-stress Arabidopsis root in the H 2 O 2 -dependent manner.…”
Section: H2s-induced Cross-adaptationmentioning
confidence: 99%
“…In addition, NaCl stress inhibited seed germination and seedling growth, but pretreatment with NaHS could significantly attenuate this inhibitive effect and increase the ratio of potassium (K) to sodium (Na) in the root parts (Wang et al, 2012). Also, under 100 mM NaCl stress, Arabidopsis roots displayed a great increase in electrolyte leakage and Na + /K + ratio, indicating that Arabidopsis was sensitive to salt stress, while treatment with NaHS enhanced the salt tolerance by maintaining a higher K + /Na + ratio (Li J. et al, 2014). In addition, the level of gene expression and the phosphorylation of plasma membrane H + -ATPase and Na + /H + antiporter protein was promoted by H 2 S, while the effect of H 2 S on the plasma membrane Na + /H + antiporter system was removed by diphenylene iodonium (DPI, a PM NADPH oxidase inhibitor) or dimethylthiourea (DMTU, an ROS scavenger) (Li J. et al, 2014), suggesting that H 2 S can maintain ion homeostasis in salt-stress Arabidopsis root in the H 2 O 2 -dependent manner.…”
Section: H2s-induced Cross-adaptationmentioning
confidence: 99%
“…The products of sulfur metabolism, such as Cys, GSH, PCs, MTs and H 2 S, have biological functions in plant responses to heavy metal stress and oxidative stress25. Recently, positive effects of H 2 S in response to several types of abiotic stress in plants have been found, such as osmotic stress, salt stress, heat shock stress and heavy metal stress26272829. It has been reported that a cross-talk between H 2 S and nitric oxide is responsible for the increased Cd 2+ tolerance in alfalfa and Bermuda grass plants3031.…”
mentioning
confidence: 99%
“…As a signaling molecule, H 2 S is active on stomatal guard cells, as has been reported in multiple studies over recent years (García-Mata and Lamattina, 2013;Hou et al, 2013;Jin et al, 2013;Li et al, 2014). One of the key regulators of guard cells is abscisic acid (ABA), which is produced in response to a variety of stresses and promotes stomatal closure.…”
mentioning
confidence: 93%